2003
DOI: 10.2134/jeq2003.1694
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Clipping and Nitrogen Management in Turfgrass on Soil Organic Carbon and Nitrogen Dynamics

Abstract: Experiments to document the long-term effects of clipping management on N requirements, soil organic carbon (SOC), and soil organic nitrogen (SON) are difficult and costly and therefore few. The CENTURY ecosystem model offers an opportunity to study long-term effects of turfgrass clipping management on biomass production, N requirements, SOC and SON, and N leaching through computer simulation. In this study, the model was verified by comparing CENTURY-predicted Kentucky bluegrass (Poa pratensis L.) clipping yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 23 publications
5
130
1
Order By: Relevance
“…The younger Kikuyu turfgrass required at least 150 kg N ha −1 yr −1 in the first 2 years after establishment, whereas the older turfgrass was maintained at an acceptable quality, albeit with less growth, without additional N fertiliser during the 24 month study. Our findings are consistent with the limited number of studies that have investigated N requirements for older turfgrass stands (Petrovic 1990;Qian et al 2003). For example, estimates based on historical data and simulation modelling indicated N requirements of Kentucky bluegrass (Poa pratensis L.) (where clippings were returned) would be maintained at 150 kg N ha −1 yr −1 for the first 10 years after establishment, and then continue to decline with age such that only 60 kg N ha −1 yr −1 would be required to maintain 51 to 100 year old turfgrass (Qian et al 2003).…”
Section: Nitrogen Leaching From Turfgrasssupporting
confidence: 90%
See 1 more Smart Citation
“…The younger Kikuyu turfgrass required at least 150 kg N ha −1 yr −1 in the first 2 years after establishment, whereas the older turfgrass was maintained at an acceptable quality, albeit with less growth, without additional N fertiliser during the 24 month study. Our findings are consistent with the limited number of studies that have investigated N requirements for older turfgrass stands (Petrovic 1990;Qian et al 2003). For example, estimates based on historical data and simulation modelling indicated N requirements of Kentucky bluegrass (Poa pratensis L.) (where clippings were returned) would be maintained at 150 kg N ha −1 yr −1 for the first 10 years after establishment, and then continue to decline with age such that only 60 kg N ha −1 yr −1 would be required to maintain 51 to 100 year old turfgrass (Qian et al 2003).…”
Section: Nitrogen Leaching From Turfgrasssupporting
confidence: 90%
“…Consequently, on average, the older turfgrass produced at least twice the total clippings dry mass of the younger turfgrass at the same N application rates (Fig. 2), and possibly as a result of the older turfgrass deriving additional N from the mineralisation of soil N in the turfgrass sod (Qian et al 2003). Increasing the N application rate to each turfgrass age increased growth.…”
Section: Turfgrass Growthmentioning
confidence: 93%
“…However,to facilitate accumulation of organic matter in lawn soils and reduce the need for fertilization, leaving clippings on site during the growing season (i.e., clipping return, or ''grasscycling''), is usually recommended (Harivandi and Gibeault 1999;Hartin and Harivandi 2001;Milesi et al 2005). Qian et al (2003) showed with a CENTURY model simulation that clipping return may increase soil sequestration of C and N by 11-59 and 12-78 %, with greater improvements under lower rather than higher fertilization rates (75 vs. 150 kg N ha -1 year -1 ); meanwhile, this practice may reduce the N requirement of lawns from 25-60 % depending on lawn age. Other studies also showed that clipping return, along with appropriate mowing frequencies, may reduce the need for fertilization (Heckman et al 2008;Kopp and Guillard 2002), preserve soil moisture (Harivandi and Gibeault 1999;Hartin and Harivandi 2001), and improve plant N uptake (Kopp and Guillard 2002); however, it might also potentially increase leaching loss of NO 3 -, especially when fertilization was not reduced or irrigation was excessive (Kopp and Guillard 2005).…”
Section: N Losses Through Gaseous and Aqueous Formsmentioning
confidence: 99%
“…In contrast, the native forest ecosystems in Baltimore had 60% higher SOC to a depth of 20 cm relative to the shortgrass steppe ecosystems in Denver. These landscape-and regional-scale comparisons have documented the baseline effects of converting native vegetation to turfgrass, but do not adequately explain the effects of management on intraregional variability [17,23]. Previous studies of urban SOC have established the basic factors affecting C storage and flux in turfgrass ecosystems [17,19,22] as well as quantified SOC contents found in residential urban areas [1,7,16,24,25].…”
Section: Introductionmentioning
confidence: 99%